#TITLE_ALTERNATIVE# - HARYADI MUSLIM (NIM 13701026), DEDI
The main purpose of this research is to investigate the microstructural changes, especially matrix phase (y solid solution), precipitate phase (intermetallic y'), and carbides of directionally-solidified nickel-base superalloys Rene 142. The SEM (Scanning Electron Microscopy) method are carried out to inspect the microstructures, whereas EDS (Energy Dispersive Spectroscopy) method for elemental characterization of each phase. Microhardness testing is implemented by Vickers method. The microstructures of as-received, root section specimen is being compared with treated ones'. The results will be analyzed in order to determine the phase behaviors as their respond to overtemperature treatment. Those behaviors are: y' phase local dissolution into phase, y' change its shape toward lamellar structure, and MC carbides decompose into M23C6 carbides, which segregates at grain boundary and form continuously (coarsen). The Vickers hardness number of root section is relatively constant, on the contrary with body section (decrease with increasing temperatures).